Chimeric antigen receptor transduced T cells: Tuning up for the next generation. Issue 9 (27th November 2017) - Schubert, Maria‐Luisa; Hoffmann, Jean‐Marc; Dreger, Peter; Müller‐Tidow, Carsten; Schmitt, Michael
Abstract : Chimeric antigen receptor (CAR) T cell therapy has recently achieved impressive clinical outcome in patients with CD19‐positive hematologic malignancies. Extrapolation of CAR T cell treatment to solid tumors, however, has not yet yielded similar results. This might be due to intrinsic causes, e.g. insufficient CAR T cell activation or CAR toxicity as well as extrinsic factors displaying an unfavorable tumor environment for CAR T cells by raising physical and chemical barriers. In this review, we discuss the advantages as well as major obstacles of CAR T cell therapy, particularly in the context of solid tumors, and focus on efforts and novel strategies in CAR T cell development.